TEXNIKA OLIY O‘QUV YURTLARI TALABALARIDA YOZISH KO‘NIKMALARINI WIKI- TEXNOLOGIYA ASOSIDA RIVOJLANTIRISH METODIKASI” (INGLIZ TILINI O‘QITISH MISOLIDA) (Scientific journal of the Fergana State University, 2024)
This article recommends the methods of developing English as a foreign language, one of the main language skills - writing skills using wiki technologies for students of technical universities. It is based on scientific facts that this method is equally useful for students of technical higher education institution and pedagogues of English language. In the process of writing the article, the author approaches mainly from the perspective of a teacher-pedagogue, and gives instructions on how and for what purpose to use wiki-technologies in the course of the lesson. In order to make the text of the article more understandable, emphasis is placed on what wiki technology actually is and how important its role is in the field of education. It also provides a brief overview of English writing skills and their level of difficulty, the benefits of teaching writing skills to students, and the types of writing skills and what these types include. In the article, special attention is given and explained to what the pedagogue should emphasize more in the process of teaching, the importance of time, the primary and secondary factors in the process of teaching writing skills. Some of the wiki-technologies that develop written speech are named in the article and their function is explained separately.